The Effects of Vertical Pay Dispersion: Experimental Evidence in a Budget Setting1. (19th September 2016) - Guo, Lan; Libby, Theresa; Liu, Xiaotao (Kelvin)
Abstract: Vertical pay dispersion is the difference in pay across different hierarchical levels within an organization (Milkovich and Newman1996 ). While vertical pay dispersion may be useful in attracting, retaining, and motivating highly skilled employees (Lazear and Rosen1981 ; Lazear1995 ; Prendergast1999 ), our study investigates a potential disadvantage; specifically, the negative impact of perceived unfairness of vertical pay dispersion on employees' budgeting decisions. We predict and find that high vertical pay dispersion motivates subordinates to misreport costs to a greater extent than low vertical pay dispersion. Furthermore, we predict and find that superiors, on average, exercise more lenient cost controls when vertical pay dispersion is high rather than low. Supplemental analysis indicates superiors are more lenient on average because of their aversion to inequity caused by vertical pay dispersion. Our results suggest that high vertical pay dispersion can compromise the overall corporate budgeting environment, where higher levels of misreporting by subordinates goes unchecked by superiors.